Two- to Four-Year Follow-up Results of Total Knee Arthroplasty Using a New High-Flexion Prosthesis - Kim, Man Soo (Knee Surg Relat Res, 2016)
PURPOSE: The purpose of this study was to evaluate minimum 2-year follow-up results of total knee arthroplasty (TKA) performed using a new high-flexion prosthesis design (LOSPA). MATERIALS AND METHODS: The 2- to 4-year results of 191 consecutive TKAs (177 patients) with the LOSPA posterior-stabilized prosthesis were evaluated. The patients were assessed clinically and radiographically using the Knee Society scoring system (KSS) and the Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC). RESULTS: The mean range of motion (ROM) increased significantly from 117.4° (range, 75° to 140°) preoperatively to 126.7° (range, 80° to 144°) postoperatively (p<0.001). The mean KSS and WOMAC scores improved significantly from 121.4 (range, 42 to 185) and 56.1 (range, 23 to 88) preoperatively to 174.0 (range, 130 to 200) and 16.4 (range, 0 to 85) postoperatively, respectively (both, p<0.001). One knee required revision for deep infection. No knee had aseptic loosening or osteolysis. Radiolucent lines were noted in 15 knees (7.9%). CONCLUSIONS: The new high-flexion total knee prosthesis resulted in no early aseptic loosening of the component and improved postoperative ROM comparable to other high-flexion TKA prostheses at 2- to 4-year follow-ups.